Calmodulin of the tropical sea cucumber: Gene structure, inducible expression and contribution to nitric oxide production and pathogen clearance during immune response. Issue 2 (August 2015) - Chen, Ting; Ren, Chunhua; Li, Wuhu; Jiang, Xiao; Xia, Jianjun; Wong, Nai-Kei; Hu, Chaoqun
Abstract: Calmodulin (CaM) is an essential second messenger protein that transduces calcium signals by binding calcium ions (Ca 2+ ) and modulating its interactions with various target proteins. In contrast to vertebrates, where CaM is well established as a cofactor for Ca 2+ -dependent physiological and cellular functions including host defense, there is a paucity of understanding on CaM in invertebrates (such as echinoderms) in response to immune challenge or microbial infections. In this study, we obtained and described the gene sequence of CaM from the tropical sea cucumber Stichopus monotuberculatus, a promising yet poorly characterized aquacultural species. mRNA expression of StmCaM could be detected in the intestine and coelomic fluid after Vibrio alginolyticus injection. Transcriptional and translational expression of Stm CaM was inducible in nature, as evidenced by the expression patterns in primary coelomocytes following Vibrio challenge. This response could be mimicked by the Vibrio cells membrane components or lipopolysaccharides (LPS), and blocked by co-treatment of the LPS-neutralizing agent polymyxin B (PMB). Furthermore, inhibition of CaM activity by incubation with its inhibitor trifluoroperazine dihydrochloride (TFP) blunted the production of Vibrio -induced nitric oxide (NO) and augmented the survival of invading Vibrio in coelomocytes. Collectively, our study here supplied the first evidence for echinoderm CaM participation in innate immunity, and provided a functional link between CaM expression and antibacterial NO production in sea cucumber. Highlights: We first cloned and described CaM gene form a tropic sea cucumber. CaM is a highly conserved and ubiquitously expressed gene. The study supplied the first evidence for echinoderm CaM participation in innate immunity. The first study for inducible expression of CaM at both mRNA and protein levels in marine invertebrates. This study provided a functional link between CaM expression and NO production in marine invertebrates.